Efektivitas Model Pembelajaran ATI Dalam Pembelajaran Sains Di Universitas Graha Nusantara Padangsidimpuan - Rizky Febriani Pohan; Muhammad Rahman Rambe (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The Aptitude-Treatment Interaction (ATI) learning model is a learning model that has a number of strategies (treatments) used to deal with each particular individual according to their respective ability levels in order to improve student learning outcomes. This study aims to determine the effect of the application of the ATI learning model on student learning outcomes in science learning and to determine the effectiveness of the ATI learning model in science learning. The sample of students studied were students of the Civil Engineering Study Program, Faculty of Engineering, Graha Nusantara University, which consisted of 2 groups. The first group was used as the experimental group (teaching with ATI) and the second group as the control group (teaching without ATI) with the number of students in each group = 20 people. The research design used was a 2x2 quasi-factorial experimental design. The data obtained were analyzed by chi-square test at a significance level of 0.05. The results showed that the experimental group's science learning outcomes increased by 49.17%, while the control group's science learning outcomes only increased by 42.25%. Thus, the ATI learning model has an effectiveness percentage of 1.67%. With the chi-square test, it can be stated that this effectiveness is due to the influence of the application of the ATI learning model.